Arabic words in medieval literary monument of Saif Saray "Gelston beat-Turki" (Journal of Oriental Studies, 2016)
This article discusses the lexico-grammatical description of Arabic words in medieval literary monument of Saif  Saray "Gelston beat-Turki". Defines the number of Arabic words in the monument, identified the phonetic, grammatical and semantic changes.
Keywords: Saif Saray; Gelston beat-Turki; language communications/connections; borrowed words; Arabic words.